Islamophobia di Kanada - Firdaus, Ilman Fajr; Lessy, Zulkipli (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
Islamophobia, as a global phenomenon, has seen significant impacts in various countries, including Canada. This research aims to investigate the dynamics of Islamophobia in Canada, explore the factors that influence public perceptions, and analyse its impact on Muslims. Using media content analysis, community surveys, and case study methods, this research identifies a number of cases of discrimination, negative rhetoric, and violence faced by Muslim communities in Canada. The study also examines how the mass media plays a key role in shaping public perceptions of Islam, as well as the extent to which government policies and regulations reflect the protection of Muslim rights. Findings highlight trends of inequality in everyday life, including in the workplace, education, and social interactions. In addition, the research discusses the efforts that have been taken by the government, Muslim community organisations to address Islamophobia. In particular, focus is given to educational initiatives and interfaith dialogue as a way to promote mutual respect in Canada's multicultural society. The study concludes by highlighting the challenges still faced by the Muslim community in Canada and emphasising the importance of cross-sectoral cooperation to create an inclusive and equitable environment for all its citizens, regardless of religious or cultural identity.